Electrochemical performance of single crystal belt-like NH4V3O8 as cathode material for lithium-ion batteries - Ottmann, Alexander; Zakharova, G. S.; Ehrstein, Benjamin; Klingeler, Rüdiger (Electrochimica acta, 2015)
NH4V3O8 with belt-like morphology has been synthesized via a hydrothermal process, using acetic acid as acidulant. The resulting phase-pure NH4V3O8 microcrystals have smooth surfaces and are typically 25-45μm long, 2-15μm wide, and 0.6-1.2μm thick. Electrochemical studies by means of cyclic voltammetry and galvanostatic cycling show that the pristine material is a suitable host for reversible Li+ de-/intercalation. Analysis of the peak currents from cyclic voltammetry by means of the Randles-Sevcik equation suggests that the Li+ de-/intercalation is diffusion-controlled with D∼5·10−15cm2s−1. The maximum discharge capacity, at 20mAg−1, amounts to 299mAhg−1. At 90mAg−1, it is still 201mAhg−1 with a capacity retention of 90% in the 100th cycle, indicating the belt-like NH4V3O8 being a promising candidate for application as cathode material in secondary lithium-ion batteries.